The ROLE OF DIGITAL LITERACY IN ENHANCING THE INFLUENCE OF DIGITAL BRANDING AND CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY AT CAFE LATERA JAMBI - Vilano, M. Afif Vilano Fitrah; Lubis, Tona Aurora; Utama, Ahmad Nur Budi (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to analyze the influence of digital branding and customer experience on customer loyalty at Cafe Latera Jambi, as well as to examine the moderating role of digital literacy in these relationships. The study employed a quantitative approach using purposive sampling of 170 Generation Z respondents who were visitors of Cafe Latera Jambi. Data were collected through a questionnaire using a 5-point Likert scale and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software. The results revealed that: (1) digital branding has a positive and significant effect on customer loyalty (β = 0.373; t = 7.037; p = 0.000); (2) customer experience has a positive and significant effect on customer loyalty (β = 0.450; t = 9.311; p = 0.000) and serves as the strongest predictor; (3) digital literacy does not moderate the effect of digital branding on customer loyalty (β = −0.078; t = 1.526; p = 0.127); and (4) digital literacy does not moderate the effect of customer experience on customer loyalty (β = −0.018; t = 0.382; p = 0.703). Although digital literacy does not function as a moderator, it has a significant direct effect on customer loyalty (β = 0.270; p = 0.000). The research model explains 44.9% of the variance in customer loyalty. These findings imply that digital branding and customer experience strategies can be applied universally to the Gen Z segment without the need for segmentation based on digital literacy levels.